1992
DOI: 10.1002/jcb.240480311
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β1 inhibits DNA synthesis and phosphorylation of the retinoblastoma gene product in a rat liver epithelial cell line

Abstract: In the rat liver epithelial cell line, WB, the ability of TGF-beta 1 to inhibit DNA synthesis was shown to correlate with its ability to inhibit phosphorylation of the protein product of the retinoblastoma susceptibility gene, pRb. When WB cells were serum-starved, then refed with serum-containing medium, a peak of DNA synthesis occurred at about 18 h. Autoradiographs showed that 43.6% of cell nuclei could be labeled with 3H-thymidine at this time. When TGF-beta 1 was added simultaneously with serum, it blocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…TG¥-fi\ is known to inhibit pho.sphorylation of pRB in rat liver epithelial cell line [16], mink lung epithelial cell [22] and human keratinocytes [23]. These results may support the hypothesis that the effect of MC903 and 1,25(OH)2D3 is closely related to pRB.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…TG¥-fi\ is known to inhibit pho.sphorylation of pRB in rat liver epithelial cell line [16], mink lung epithelial cell [22] and human keratinocytes [23]. These results may support the hypothesis that the effect of MC903 and 1,25(OH)2D3 is closely related to pRB.…”
Section: Discussionsupporting
confidence: 65%
“…Its gene was first discovered to be a gene in which mutational inactivation resulted in the development of ocular tumors in children [10]. The pRB is dephosphorylated in Gl phase and becomes multiplephosphorylated near the Gl/S boundary; it remains highly phosphorylated through G2 and early M. Then pRB is dephosphorylated as the cell moves into late M or early Gl phase [13][14][15][16]. In addition, pRB is involved in the growth regulation of normal eells, namely cell eyele regulation.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β can function as a tumor promoting factor by increasing cell metastatic motility, survival ability, and angiogenesis. About two decades ago, the most widely known cellular effect of TGF-β was the induction of cell cycle arrest that led to the inhibition of the proliferation of many normal epithelial cell types [16][17][18]. Similarly, the apoptosis induction effect of TGF-β in normal epithelial cells has also been identified during that period [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned previously, inhibition of epithelial cell proliferation by TK3F-B at the GI/S transition is accompanied by dephosphorylation of the retinoblastoma gene product (pRB) (Laiho et al 1990, Whitson & Itakura 1992 which implies at least some role for phosphatases. Hyperphosphorylated pRB binds less tightly to nuclei than does the growth-inhibitory hypophosphorylated form (Templeton 1992) and is more easily extracted (Mittnacht & Weinberg 1991).…”
Section: New Insights Into Protein Phosphorylation/ Dephosphorylationmentioning
confidence: 93%
“…Inhibition, by TGF-/3, of epithelial cell proliferation at the G,/S transition is accompanied by dephosphorylation of the retinoblastoma gene product (pRB) (Laiho et al 1990, Whitson & Itakura 1992) and a decrease in the histone H1 kinase activity of ~3 4 '~'~ (Howe, Draetta & Leof 1991). Northern blot analysis of human keratinocytes (Geng & Weinberg 1993) revealed that EF-B could suppress cell cycle progression in two distinct ways.…”
Section: Epifqnova and R F Brooksmentioning
confidence: 99%